PELAKSANAAN FUNGSI SOSIAL RUMAH SAKIT DALAM MENYEDIAKAN SARANA PELAYANAN BAGI MASYARAKAT MISKIN BERDASARKAN PERATURAN MENTERI KESEHATAN NOMOR 4 TAHUN 2018 TENTANG KEWAJIBAN RUMAH SAKIT DAN KEWAJIBAN PASIEN (STUDI KASUS DI RSU SUAKA INSAN BANJARMASIN) - Maria Thersia; Sabda Wahab; Irman Idrus; Ria Wulandari (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
Hospitals as one of the service facilities in the health sector have the obligation to carry out social functions for the poor as regulated in Law Number 44 of 2009 concerning Hospitals and their implementation through Regulation of the Minister of Health Number 4 of 2018 concerning Hospital Obligations and Patient Obligations. Hospitals do not only serve people who are able or rich, but hospitals are obliged to provide health service facilities intended for the poor through the provision of health services for underprivileged patients, emergency services without a down payment, free ambulances, services for victims of natural disasters and external events. ordinary, and social service for humanitarian missions. This study uses a sociological juridical method with analytical descriptive. The type of data used is the type of primary data and secondary data. Methods of data collection is done by literature study and field study. Field studies were conducted by interviewing respondents and resource persons. Analysis of the data used is a qualitative analysis. The result of the research is that although it does not partner with the Health Insurance Administration Agency (BPJS), the implementation of social functions in providing health service facilities for the poor is still carried out by the Banjarmasin Insan Asylum General Hospital. The social function is carried out through the provision of service facilities by providing class III treatment rooms with 32 beds out of 167 available beds for poor patients. Patients who are treated in class III get a charity discount of 50%-100%. An additional 25%-50% discount for laboratory examinations, emergency services without a down payment, providing free ambulances for underprivileged patients, carrying out social services and health promotion in remote areas of South Kalimantan according to the ability of the Hospital. However, the implementation of the Hospital's social functions has been hampered due to space and financial constraints, the decrease in the number of patients as a result of the Hospital's non-partnership with the Social Security Administering Body (BPJS), patients do not pay or pay for treatment costs, so that the implementation of the Hospital's social functions becomes difficult. not optimal.